Fractal Deposits of a Hemostatic Hydrophilic Polymer in Mohs Micrographic Surgery Frozen Sections: A Histologic Analysis and Comparison With Sodium Polystyrene Sulfonate (Kayexalate). (April 2020) - Urman, Danielle; Ledon, Jennifer; Kolker, Steven; Bennett, Richard G.
Abstract : Abstract: Hydrophilic polymer with potassium ferrate (HPPF) powder is available as an over-the-counter hemostatic agent used by patients to stop superficial bleeding. In dermatology, it is applied to stop bleeding after superficial shave or punch biopsies or in open wounds after Mohs micrographic surgery. Despite its widespread availability, however, HPPF in histopathologic skin sections is highly unusual. We noted HPPF in skin closely resembles sodium polystyrene sulfonate (SPS) seen in colonic necrosis; SPS is a potassium binder given orally or rectally in hyperkalemic patients with end-stage renal disease. We describe the in vivo and in vitro histologic appearance of HPPF, compare HPPF with SPS, and discuss its potential migration into blood or lymph vessels.